2005
DOI: 10.1007/s10517-005-0379-y
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Mechanisms of Antiarrhythmic Effect of Quaternidine

Abstract: Complex electrophysiological study of the effects of quaternidine carried out on intact hearts from cats, myocardial fragments from rats, and single ionic channels of large edible snail showed that quaternidine demonstrates properties of class 1B antiarrhythmic drug according to Vaughan-Williams nomenclature. This agent did not suppress nomotopic pacemaker automaticity, did not change conduction in ventricles, atria, and atrioventricular junction in hearts with preserved sinus rhythm, did not prolong refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…3*HCl, is a local anaesthetic that has antiarrhythmic effects. [15][16][17] In the present study, new ionic compounds were prepared via N-alkylation of tolperisone, diphenhydramine and trimecaine with alkyl halides (Scheme 1, Table 1). Since some of the synthesized ionic compounds have been proven to stimulate plant growth, [18,19] the ecotoxicity and myelostimulating [20] data for these substances is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…3*HCl, is a local anaesthetic that has antiarrhythmic effects. [15][16][17] In the present study, new ionic compounds were prepared via N-alkylation of tolperisone, diphenhydramine and trimecaine with alkyl halides (Scheme 1, Table 1). Since some of the synthesized ionic compounds have been proven to stimulate plant growth, [18,19] the ecotoxicity and myelostimulating [20] data for these substances is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies focusing on lidocaine (dimethylacetamide) derivatives have intensified in Russia. In a series of studies, their antiarrhythmic medication (Blinov and Kostin 2003;Blinov et al 2014;Sernov et al 2005) and the anti-ischemic (Kostin et al 2003) activities were studied, and it was shown that the derivatives exceed their structural ancestor both by duration and by efficiency in experimental animals (Blinova et al 2015) and in vitro (Balashov et al 2005). All this served as the basis for assuming that this group of amino acid-substituted and quaternary derivatives of dimethylacetamide had a local anesthetic activity, which determined the relevance of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they would lose their antiarrhythmic property. In addition, it should be emphasised that an increased effect duration is accompanied by the molecule haemodynamic profile optimisation (Balashov et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Quaternary DPA derivatives were produced by targeting the nitrogen of the aliphatic fragment of the molecule by analogy with developing a national antiarrhythmic drug quaternin, which is a quaternary allylmorpholinic derivative of Trimethylphenylacetamide (Balashov et al 2005). The new substance appeared to be more active than Lidocaine and possessed a promising antiarrhythmic effect.…”
Section: Introductionmentioning
confidence: 99%